Parental Involvement in the Preoperative Surgical Safety Checklist Is Welcomed by Both Parents and Staff - Martin T. Corbally; Eamon Tierney (International Journal of Pediatrics)
We involved the parents of paediatric patients in the first part of the three-stage WHO Surgical Safety Checklist (SSC) process. Forty-two parents took part in the study. They came to the theatre suite with their child and into the induction room. Immediately before induction of anaesthesia they were present at, and took part in, the first stage of the three-stage SSC process, confirming with staff the identity of their child, the procedure to be performed, the operating site, and the consent being adequately obtained and recorded. We asked parents and theatre staff later whether they thought that parental involvement in the SSC was beneficial to patient safety. Both parents and staff welcomed parental involvement in the WHO Surgical Safety Checklist and felt that it improved patient safety.